Application of Multiliteracies Pedagogy in Teaching English at Early Grades in Nepal - Ghimire, Nani Babu (Journal of NELTA, 2020)
The purpose of the study was to explore practices of the teachers in teaching English at early grade through multiliteracies pedagogy in Nepal. The study was conducted in a community school in the central hilly district by adopting a critical ethnography research design in order to capture the rich and in-depth ideas of three teachers at early grade through ‘in-depth interviewing’. Interviews were audio-recorded, recorded data were transcribed assigning codes and three main themes were developed in terms of the codes during the data analysis process. The findings exposed that the teachers have engaged in bilingual practice using Nepali and English languages instead of creating multilingual space using students’ home language even if they belong to various ethnic groups such as Majhi, Danuwar, Tamang, Magar, and Newar. They have been adopting print literacy as teaching-learning practice such as reading the textbooks and asking the students to write the exercises of the textbook but they rarely use modern technology based multi-modal literacy. The school administration needs to be conscious to apply multiliteracies pedagogy by strengthening the capacity of the teachers on it. Likewise, the school has to establish a basic ICT lab with an internet facility enhancing teachers’ skills to use it appropriately.